Analysis of critical satellites for ground-based augmentation system approach service type E - Alhosban, Ahmad (International Journal of Innovative Research and Scientific Studies, 2025)
The Ground-Based Augmentation System (GBAS) Approach Service Type C and D, GAST-C/D, has been standardized and recently certified at many airports to support landing operations in aviation since 2012 and 2018, respectively. GBAS landing services use Single-Frequency and Single-Constellation (SFSC), either GPS L1, GLONASS L1, or Galileo E1. However, the advanced GBAS performance, GAST-E, requires the use of Dual-Frequency Dual-Constellation (DFDC) GPS/Galileo L1/E1, which has not been standardized yet. Moreover, the number of critical satellites is a determining factor for GBAS availability in its standardization process. This paper aims to simulate the required allowable number of critical satellites to achieve GAST-E performance using GPS L1 and Galileo E1 frequencies. A validated simulation tool used in a previous study has been reused for this purpose. The results show the feasibility of achieving GAST-E with 6 critical satellites, down from the 10 that were standardized for GAST-C. A further investigation using 2 critical satellites was also proposed. Results show that a change of 4 critical satellites, more or less than 6, would cause a change of nearly 45% in GBAS system availability. Consequently, this research would pave a step ahead in the standardization process for the higher performance of GBAS-based navigational instruments.